Biloma: An Unusual Complication in a Patient With Calculus Cholecystitis - Sharma, Prakash; Neupane, Phanindra; Poudel, Ramesh (Nepalese Journal of Radiology, 2018)
A biloma is an encapsulated collection of bile located in the abdomen. It usually occurs spontaneously or can be secondary to traumatic injury (hepatobiliary surgery) and in rare condition it can occur as complication of cholecystitis and cholangiocarcinoma. The diagnosis can be suggested on the basis of patient’s medical history, clinical symptoms and imaging findings but final definitive diagnosis can only be made by aspiration of the content and biochemical analysis. We here report a case of 62 years male patient admitted with acute abdominal pain in the right hypochondrium caused by a spontaneous biloma. We discuss the role of the various diagnostic imaging techniques, particularly which of ultrasound and CT. The biloma was identified on computed tomography in this case.